Fabrication and Investigation of Nanostructured Monolayer Porous Silicon (PSi) Based for Silicon Solar Cell Applications - Salih, Saad A. Mohammed; kadhim, Mayameen S. (Nahrain University College of Engineering Journal, 2017)
Fabrication of PSi is generated successfully depending upon photo-electrochemical etching process. The purpose is to differentiate the characterization of the PSi monolayer based on c-silicon solar cell compared to the bulk silicon alone. The surface of ordinary p-n solar cell has been reconstructed on the n-type region of (100) orientation in order to enhance the conversion efficiency. The process relied on varying the etching time with fixed current density. The other process conditions were kept constant, for instance, HF concentration, current density, temperature,etc. The role of different laser types and powers illuminated the n-region has been realized. In particular, the blue laser (473nm of two powers 50 and 100mW) appears to be the most operative wavelength to obtain the optimum efficiency and pore sizes as well as the etching rate. The samples were tested and characterized by the (I-V)Measurement and analyzed by SEM, PL and AFM tests. The obtained solar cell efficiency was in the range of 11% compared to the typical solar cell efficiency which was (3.34%).